Corporate social responsibility in labor relations: mapping the use of fuzzy logic with iramuteq software - Mannarelli Filho, Teucle [UNESP]; Baptista, Renato Dias [UNESP]; Gabriel Filho, Luis Roberto Almeida [UNESP] (Ludomedia Unipessoal Lda, 2022)
Social responsibility gains importance and space in academic discussions and in society itself, given the speed of global changes; specifically, in debates around social responsibility in work relations in companies and their surroundings in society, in consequence of economic globalization and pressure from consumers with products and services produced with social responsibility. From this context emerged the problematic and objective of this study to present a mapping of the use of fuzzy methodology, in the analysis of corporate social responsibility in labor relations in the world. This mapping used a literature review in the period from 2013 to 2020, with textual word analysis through textual software use. Methodologically, the Iramuteq software was used, with 11 texts selected on: 1) similitude analysis, 2) descending hierarchical classification by classes and 3) word cloud. The results reached the proposed objectives, and the restrictions of the study are linked to the subjectivity in the choice of search keywords for the selected articles and to the final selection of the articles used to compose the textual corpus of software analysis. There are, as well, new lines of research related to measuring companies' social responsibility in labor relations.
A responsabilidade social empresarial nas relações do trabalho: mapeamento do uso lógica fuzzy com o software Iramuteq
Keywords: Fuzzy; Iramuteq; Labor relations; Social responsibility